1990
DOI: 10.1002/1097-0142(19900615)65:12<2657::aid-cncr2820651210>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of cyproheptadine in cancer patients with anorexia and/or cachexia

Abstract: Anorexia, cachexia, and resultant weight loss are major clinical problems in a substantial proportion of patients with advanced cancer. Effective means of alleviating these problematic symptoms are lacking. Extensive clinical data demonstrate a weight enhancing effect for the serotonin antagonist, cyproheptadine, in several clinical situations. In addition, sound basic research suggests that cyproheptadine may be helpful in patients with cancer anorexia/cachexia. Because of this, the authors performed a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(64 citation statements)
references
References 22 publications
3
57
0
4
Order By: Relevance
“…Cyproheptadine was commonly associated with an increase in appetite, unsurprisingly because it has been prescribed in other populations as an appetite stimulant. 28,29 The most commonly reported side e ect during the baclofen period was a feeling of drowsiness or somnolence, consistent with other reports. 30,31 The side e ects of drowsiness and fatiguability with any of the drugs were not visible to the experimenters, nor did they interfere with performing evaluations, except when the drug period could not be completed.…”
Section: Subjects With Functional Overground Reciprocal Walkingsupporting
confidence: 80%
“…Cyproheptadine was commonly associated with an increase in appetite, unsurprisingly because it has been prescribed in other populations as an appetite stimulant. 28,29 The most commonly reported side e ect during the baclofen period was a feeling of drowsiness or somnolence, consistent with other reports. 30,31 The side e ects of drowsiness and fatiguability with any of the drugs were not visible to the experimenters, nor did they interfere with performing evaluations, except when the drug period could not be completed.…”
Section: Subjects With Functional Overground Reciprocal Walkingsupporting
confidence: 80%
“…Clinical studies have also shown that it is not possible to reverse the wasting process in cancer patients by nutritional supplementation. These studies include dietary counseling (198), total parenteral nutrition (TPN) (69) or appetite stimulants such as cryoheptadine (127), a histamine antagonist with antiserotonergic and appetite stimulatory effects, or dronabinol, the active ingredient in marijuana (267). Moreover, with TPN, any weight gain is transient, and body composition analysis shows that this is fat and water rather than lean body mass (69).…”
Section: A Anorexiamentioning
confidence: 99%
“…Thus cyproheptadine, a histamine antagonist with antiserotonergic and appetite-stimulating effects, produced only a slight improvement in appetite and did not significantly prevent progressive weight loss in anorectic cancer patients (127). Marijuana is known to stimulate appetite and weight gain, but a clinical study of dronabinol, the active ingredient, failed to halt the progressive loss of body weight of cachectic cancer patients, although a subjective improvement in mood and appetite was observed (267).…”
Section: A Agents Affecting Appetitementioning
confidence: 99%
“…88 Both medications are associated with significant side effects, particularly central nervous system toxicity. 88,94,95 Among anabolic agents, a 4-week randomized trial of human growth hormone in 20 undernourished elderly people demonstrated slightly faster weight gain and improved walking time in those receiving the hormone. After 4 weeks, between-group differences in weight were no longer statistically significant.…”
Section: Pharmacologic Therapy To Reverse Weight Lossmentioning
confidence: 99%